2021
DOI: 10.1183/13993003.04015-2020
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term impact of COVID-19 on pulmonary function, functional capacity and quality of life

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) has spread worldwide determining a dramatic impact on the healthcare system. Aim of this study is to evaluate mid-term clinical impact of COVID-19 on respiratory function.Methods379 patients were evaluated 4 months after SARS-COV-2 diagnosis. Patients were divided in two groups based on the presence of pneumonia during COVID. Clinical conditions, quality of life, symptomatology, 6-min walking test, pulmonary function test with spirometry and diffusing capacity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
180
9
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(215 citation statements)
references
References 19 publications
20
180
9
6
Order By: Relevance
“…These different definitions can influence the capacity of DL CO to predict the functional sequelae of the different variables analysed. However, as we observed in this present work, and consistent with the results from the only published study that evaluated patients six months after infection with SARS-CoV-2 [33], these variables are usually associated with parameters related to the severity of the pneumonic episode (e.g., prognostic scales, value of analytical determinations indicative of greater inflammation) and intensity of the supportive therapy required during patient admission [1][2][3][4][5][6][7][8]. One study found that cardiorespiratory comorbidities and female sex predicted DL CO < 80%, but not DL CO < 60% [7].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These different definitions can influence the capacity of DL CO to predict the functional sequelae of the different variables analysed. However, as we observed in this present work, and consistent with the results from the only published study that evaluated patients six months after infection with SARS-CoV-2 [33], these variables are usually associated with parameters related to the severity of the pneumonic episode (e.g., prognostic scales, value of analytical determinations indicative of greater inflammation) and intensity of the supportive therapy required during patient admission [1][2][3][4][5][6][7][8]. One study found that cardiorespiratory comorbidities and female sex predicted DL CO < 80%, but not DL CO < 60% [7].…”
Section: Discussionsupporting
confidence: 90%
“…As shown in the table summarising these studies (Table 7), and despite the fact that there is little variation in the percentage over the reference value of DL CO , when the alteration was defined by a decrease under 80% in the theoretical percentage (51-57%), except for series that include only post-ICU patients [10]; however, when this was measured as a decrease below the LLN, DL CO alteration ranged from 17% in our work to 24% as reported by Lerum et al [1], and 34% in another study nine weeks after discharge [32]. In other studies, the relationship between predictor variables and lung involvement was enhanced by different linear correlation analyses without defining specific cut-off points for the definition of DL CO alteration [6,8].…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations